1998
DOI: 10.1530/jrf.0.1120357
|View full text |Cite
|
Sign up to set email alerts
|

Dog epididymis-specific mRNA encoding secretory glutathione peroxidase-like protein

Abstract: A differential library screening procedure was used to clone a novel abundant and tissue-specific cDNA from the dog epididymis. It was tentatively named CE7 for dog epididymal gene product 7. By sequence similarity to homologous counterparts expressed in mice, rats, pigs, and macaque monkeys, it appears that the 1.5 kb dog epididymal mRNA encodes the secretory glutathione peroxidase-like protein, GPX5. This protein is very similar to the family of glutathione peroxidase enzymes, but does not contain selenocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…One difficulty of this 'gene-specific' library screening approach lies in the high degree of species specificity, that is, poor evolutionary conservation of many epididymal proteins. In addition, there are considerable species differences in the protein content of the epididymal fluid in various mammals (Beiglböck et al, 1998), although at least the most abundant proteins do appear to be shared.…”
Section: Molecular Cloning Approach Based On Gene-specific Probesmentioning
confidence: 99%
“…One difficulty of this 'gene-specific' library screening approach lies in the high degree of species specificity, that is, poor evolutionary conservation of many epididymal proteins. In addition, there are considerable species differences in the protein content of the epididymal fluid in various mammals (Beiglböck et al, 1998), although at least the most abundant proteins do appear to be shared.…”
Section: Molecular Cloning Approach Based On Gene-specific Probesmentioning
confidence: 99%
“…A canine epididymal cDNA library constructed in the Lambda UniZAP‐XR vector (Stratagene, LaJolla, Calif; Ellerbrock et al, 1994) was screened employing a hybridization strategy essentially as previously described (Beiglböck et al, 1998). Briefly, approximately 10 000 independent cDNA clones were plated at low density (approximately 500 plaque‐forming units per plate) and screened by a multistep procedure employing 32 P‐radiolabeled single‐stranded cDNA pools from canine epididymis to provide positively hybridizing signals and from liver, testis, and lung as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to bulls (MOURA et al, Ciência Rural, v.46, n.5, mai, 2016. 2010), some evidence suggests that GPx is present in canine epididymal secretions (BEIGLBOCK et al, 1998), and a greater activity of this enzyme was reported in samples collected from the cauda of the epididymis than in samples collected from the other segments (caput and corpus) and in the three ejaculated fractions. Therefore, this result indicates that the epididymis may be the main source of GPx in canine semen (ANGRIMANI et al, 2014b).…”
Section: Proteins Of the Canine Spmentioning
confidence: 99%